A novel gas pipeline burst detection and localization method based on the FBG caliber-based sensor array. (February 2020) - Wang, Jiajian; Ren, Liang; Jiang, Tao; Jia, Ziguang; Wang, Guo-xin
Highlights: A novel FBG caliber-based sensor is developed to accurately measure NPW signals. The sensor provides nondestructive burst detection in a pressurized pipeline. The leak localization formula is proposed that is independent of NPW velocity. A novel algorithm is presented to accurately measure NPW arrival time. The proposed method has excellent accuracy and stability in pipe leak localization. Abstract: This paper presents a novel gas pipeline burst detection and localization method eliminating the negative pressure wave (NPW) velocity and improving the leak localization accuracy. For burst detection, a novel fiber Bragg grating (FBG) caliber-based sensor is developed that can accurately measure NPW signals. Based on the sensor array, a leak localization formula is proposed that is only dependent on the sensor spacing and NPW arrival time. A novel linear fitting-based NPW knee point identification algorithm is proposed to measure the NPW arrival time more accurately and quickly to obtain the highest localization accuracy. To validate the effectiveness of the presented method, simulation tests of a high-pressure gas pipe leak are carried out on a pipe leak test platform. The test results show that the average localization error is 1.1 m and the standard deviation of the errors is 0.43. Furthermore, the localization accuracy is stable for different sensor spacings.